Kadar Serum Glutamate Piruvat Transaminase (Alt) Pada Pengonsumsi Minuman Beralkohol Di Kecamatan Banama Pulang Pisau Kalimantan Tengah - Fera Sartika; Yessy Prissilia (Jurnal Surya Medika (JSM), 2017)
The liver plays an important role in detoxifying chemicals that are not useful or harmful to the body. There are many factors that affect liver damage, such as viruses, bacteria, toxicity from drugs and chemicals and excessive alcohol consumption. Alcohol consumption over a long period of time with a certain amount can cause various diseases, one of which is liver dysfunction such as alcoholic liver disease. Disruption of the mechanism in the liver can result in swelling with an increase in liver transaminase enzymes produced, namely Alanine Aminotransferase (ALT) or Aspartate aminotransferase (AST), but more specific Alanine Aminotransferase (ALT) tests are carried out because these enzymes are produced in the liver, so that this enzyme can be used to assess abnormalities or disorders of liver function. The results of the examination of serum ALT levels consuming alcoholic beverages ranged from 12-86 U / I, where the normal ALT levels from 30 samples were 28 people, namely 93.33%, and ALT levels were more than normal as much as 2 people, namely 6.67%.